2009
DOI: 10.1039/b904731j
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous resonances in 29Si and 27Al NMR spectra of pyrope ([Mg,Fe]3Al2Si3O12) garnets: effects of paramagnetic cations

Abstract: In oxide and silicate materials, particularly naturally-occurring minerals with contents of iron oxides greater than a few percent, paramagnetic impurities are well-known to broaden MAS NMR peaks, decrease relaxation times, and even cause overall loss of signal intensity. However, detection of resolved, discrete peaks that are shifted in frequency by nearby unpaired electron spins is rare in such systems. We report here high-resolution (27)Al and (29)Si spectra for synthetic and natural samples of pyrope garne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 42 publications
(165 reference statements)
1
9
0
1
Order By: Relevance
“…27 This was actually observed for the 29 Si relaxation in aluminosilicates containing dilute Fe ions. 28 In our case, the 100% abundance and the high gyromagnetic moment of 31 Nd content. In the range x = 0 to 10 at% (inset of Fig.…”
Section: Nmrmentioning
confidence: 49%
See 1 more Smart Citation
“…27 This was actually observed for the 29 Si relaxation in aluminosilicates containing dilute Fe ions. 28 In our case, the 100% abundance and the high gyromagnetic moment of 31 Nd content. In the range x = 0 to 10 at% (inset of Fig.…”
Section: Nmrmentioning
confidence: 49%
“…As a matter of fact, MAS is expected to inhibit the secular dipole-dipole coupling that insures a common spin temperature and an exponential relaxation through nuclear spin diffusion. In that case, the through-space dipolar coupling between the nuclear spins and the randomly distributed magnetic ions should give rise to ๏ข = 0.5 27 .This was actually observed for the 29 Si relaxation in aluminosilicates containing dilute Fe ions 28 . In our case, the 100% abundance and the high gyromagnetic moment of 31 P prevented a complete vanishing of the spin diffusion mechanism.…”
Section: P Nmr Relaxationmentioning
confidence: 56%
“…These extra peaks are "paramagnetically shifted" (i.e., NMR frequency shifts that can be either positive or negative, caused by unpaired electrons of paramagnetic cations) and are due to either through-space dipolar couplings from an asymmetric cation site ("pseudo-contact shift") and/or to through-bond transfer of unpaired electron spin density to the observed nuclide ("Fermi contact shift") (Grey et al 1989(Grey et al , 1990. These effects are highly sensitive to interatomic distances and to electron distributions, and hence on structural details such as bond distances and angles (Lee et al 1998;Middlemiss et al 2013), and have been clearly detected in first and in some cases second cation shells, i.e., up to four bonds away from an observed NMR nuclide such as 29 Si, 31 P, or 27 Al in phases such as zircon, garnets, pyroxenes, MgSiO 3 perovskites, and monazites/xenotimes (Dajda et al 2003;Bรฉgaudeau et al 2009Bรฉgaudeau et al , 2012Stebbins and Kelsey 2009;Stebbins 2011a, 2011b;Palke et al 2012Palke et al , 2013Palke et al , 2015. Although it remains difficult to predict the magnitude and even the sign of paramagnetic frequency shifts from a hypothesized structure (e.g., a distribution of paramagnetic cations), geometric relations, relative frequency shifts, and observed peak areas can provide useful clues as to at least partial assignment of such peaks to given structural configurations.…”
mentioning
confidence: 97%
“…Their high symmetry means only one crystallographic site each for a dodecahedrally, octahedrally, and tetrahedrally coordinated cation, and the NMR spectra of the pure compounds are correspondingly simple (MacKenzie & Smith, 2002;Florian et al, 2001). However, in homogeneous large natural crystals of pyrope garnet with low contents of ferrous iron (Mg 3 Al 2 Si 3 O 12 , FeO contents of 1 to 3%), both 29 Si and 27 Al MAS NMR first revealed several additional peaks within normal chemical shift ranges, then an extra 29 Si peak almost 200 ppm above this known range (Stebbins & Kelsey, 2009). Variable-temperature studies confirmed that all of these were paramagnetically shifted peaks caused by the unpaired spins in the Fe 2+ (Figs.…”
Section: Garnetsmentioning
confidence: 99%